Surgical treatment of cardiac metastases: analysis of a 13-year single-center experience - Mkalaluh, Sabreen; Szczechowicz, Marcin; Torabi, Saeed; Sabashnikov, Anton; Mashhour, Ahmed; Karck, Matthias; Weymann, Alexander (The thoracic and cardiovascular surgeon, 2019)
Background Cardiac metastases are more common than primary malignant tumors of the heart and are usually treated surgically as a palliative approach. In this study, we reviewed our experience with the surgical treatment of patients with cardiac metastases of various types of malignant tumors. - - Methods Between 2003 and 2016, 10 patients underwent surgery for cardiac metastases at our institution. - - Results The mean age was 53.5 ± 19 years. Female patients made up 60% (n = 6) of the collective. The cohort included cardiac metastases of diverse origins (peripheral sarcomas, melanoma, rectal carcinoma, and hepatocellular carcinoma). The left side of the heart was more frequently affected (n = 7). In only six patients, the primary malignancy was known at the time of cardiac surgery. The interval between the first diagnosis of the primary tumor and cardiac metastases ranged from simultaneous diagnosis to up to 19 years. At the time of the diagnosis of the cardiac metastases, seven patients already had multiple metastases: all seven patients had pulmonary metastases, and three of them additionally had hepatic, cerebral, or osseous metastases. Only four patients were symptomatic (atrial fibrillation, pericardial effusion, tachycardia with chest pain, dyspnea). There was no in-hospital death. The postoperative course was uneventful overall. The one- and two-year survival rates were similar, that is, 76%. The median follow-up time was 5.4 years. - - Conclusions Surgical intervention for treating cardiac metastases is associated with uneventful clinical outcome and acceptable survival in this critically ill population. Control of the primary malignancy, and maybe other metastases, determines the survival.